Effect of Lead on the Bioenergetics of the Isolated Human Monocytes - Omar, Ulfat M.; Elmorsy, Ekramy M. (Pakistan Journal of Medical & Health Sciences, 2022)
Objectives: Lead (Pb) is widely-occurring metals with known immunotoxic properties that are frequently found in the environment. The current study was conducted to evaluate the lead induced bioenergetic disruption as underling mechanism of its immunotoxic effect on the isolated human peripheral blood monocytes (hPBM). Methods: The cytotoxic effect of Pb on hPBM was evaluated by MTT assay using concentration range from o.1 to 1000 μM. The effect of lead on the phagocytic activity of the isolated cells was evaluated. Finally, the effect of lead on the bioenergetics of hPBM was evaluated by studying its effect on ATP production as well as the activities of mitochondrial complex I and III. Finally the protective effect of co-enzyme Q10 on the hPBM phagocytic activities was studied. Results: Data showed that Pb was toxic to the isolated cells in a concentration and exposure duration dependent pattern with parallel decreases in the phagocytic activities of the isolated hPBM. Lead was shown to cause significant decreases in ATP production in the exposed hPBM with significant inhibitory effect on the mitochondrial complex I and III activities. Interestingly, co-enzyme Q10 showed significant protective effect on the isolated cells phagocytic activities. Conclusion: It can be concluded that some of the immunotoxic effects that the metals Pb can impart on the functionality of isolated hPBM (i.e., phagocytic activity,) may be secondary to an induced disruption of hPBM cell bioenergetics.